الحماية القانونية للطفل من الاشهارات التجاريّة - ديرم, سومية (جامعة الوادي University of Eloued, 2019)
يحظى الإشهار التجاري بقدر كبير من الاهتمام في مجال الإنتاج والتوزيع، فهو يعد من أهم الوسائل التي يلجأ لها لترويج السلع والخدمات، حيث تصرف ميزانيات ضخمة سنويّا على الصناعة الإشهاريّة، ويرجع في ذلك للمتخصصين لجعلها أكثر جاذبية وتأثيرا، مستهدفين بذلك كل فئات المجتمع. ولقد أدركت الشركات والمعلنون أنّ الأطفال عناصر اقتصادية فاعلة متزايدة الأهمية، فأصبحوا يركزون على هذه الفئة لدفعهم إلى اقتناء منتجاتهم أو جعلهم يؤثّرون على قرارات العائلة أثناء التسوّق. ورغم خطورة الإعلان الموجه للأطفال بصفة عامة بالنظر إلى هشاشتهم وضعف إدراكهم، إلّا أنّ الخطورة تزداد بالنسبة لتسويق المنتجات الغذائية، إذ يصبح الأمر متعلقا مباشرة بصحة الطفل وسلامة نموه، خاصة وأنّها تعرض في شكل جذاب ومحبّب للأطفال ممّا يدفعهم للإفراط في الاستهلاك الضار. وهو ما يجعلنا نتساءل عن قدر الحماية التي يمكن توفيرها للطفل من الإشهارات التجارية. The Commercial advertising is of great interest in the field of production and distribution and is one of the most important means of promoting goods and services. Indeed, huge sums are spent annually in the advertising sector by specialists, to give it more attraction and effect, targeting all categories of society. Businesses and advertisers have realized that children are increasingly important economic actors and have focused on this category to get them to buy their products or to influence family decisions by shopping. Despite the delicacy of advertising aimed at children in general, given their vulnerability and low awareness, the risk increases with respect to the marketing of food products because it is directly related to the health and healthy growth of children, especially as it is presented in an attractive and enticing form, which leads to excessive harmful consumption. This raises the question of what protection can be afforded to the child against commercial advertisements.
Legal Protection Of Child From Commercial Advertising
Keywords: الإشهارات التجارية ; التسويق ; المعلنون ; وسائل الإعلام ; حماية الطفل; Commercial advertising ; marketing ; Advertisers ; media ; Child Protection